Tregs in Autoimmunity: Insights Into Intrinsic Brake Mechanism Driving Pathogenesis and Immune Homeostasis - Bednar, Kyle J.; Lee, Jee Ho; Ort, Tatiana (Frontiers in Immunology, 2022)
CD4+CD25highFoxp3+ regulatory T-cells (Tregs) are functionally characterized for their ability to suppress the activation of multiple immune cell types and are indispensable for maintaining immune homeostasis and tolerance. Disruption of this intrinsic brake system assessed by loss of suppressive capacity, cell numbers, Foxp3+ expression leads to uncontrolled immune responses and tissue damage. The conversion of Tregs to a pathogenic pro-inflammatory phenotype is widely observed in immune mediated diseases. However, the molecular mechanisms that underpin the control of Treg stability and suppressive capacity are incompletely understood. This review summarizes the concepts of Treg cell stability and Treg cell plasticity highlighting underlying mechanisms including translational and epigenetic regulators that may enable translation to new therapeutic strategies. Our enhanced understanding of molecular mechanism controlling Tregs will have important implications into immune homeostasis and therapeutic potential for the treatment of immune-mediated diseases.